Neuroanatomy of Gryposuchus neogaeus (Crocodylia, Gavialoidea): a first integral description of the braincase and endocranial morphological variation in extinct and extant gavialoids - Bona, Paula (2017)
Fil: Bona, Paula. División Paleontología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina